Enough of the chit-chat: A comparative analysis of four AI chatbots for calculus and statistics (Journal of Applied Learning and Teaching, 2023)
This article presents a comparative analysis of four AI chatbots with potential utilization in the fields of mathematics education and statistics, namely ChatGPT, GPT-4, Bard, and LLaMA. Our objective is to evaluate and compare the features, functionalities, and potential applications of these platforms within the domains of calculus and statistics. By examining their strengths and limitations, this study aims to provide insights into the selection and implementation of AI chatbots in calculus and statistics to enhance student learning. The results of the comparative analysis reveal that, while not perfect, GPT-4 outperforms ChatGPT, Bard, and LLaMA as a learning tool in calculus and statistics. Findings also reveal that chatbots may have a positive transformational impact on higher education.